上古汉语的“V于NP”结构"V于NP" = Construction in old Chinese - 朱元 Choo, Yuen (2009)
介词“于”在上古汉语中有许多语法功能，但现有的研究仍未有效地对它的语法功能作出一个统一解释，而一般把“于” 分析为一个介词，其语法作用是把宾语介绍给谓语。董秀芳（2006）则借鉴 Hopper & Thompson（1980）的“及物性假说”（Transitivity Hypothesis），认为“V 于 NP”结构中的“于”标记了动名之间的低及物关系。这个看法极具意义，但是由于董秀芳认为“于”完全无法引入受事，因此就把“于”的介宾词组和形式语法中的附加语（Adjunct）直接加以联系。正因为建立了这种联系，董秀芳又进一步认为“于”所引进的都是间接题元，而这里的间接题元就包括了处所、时间、工具、原因等非核心的语义角色。本文赞同董秀芳处理“于” 的思路，但是对于该如何运用“及物性假说”和形式语法来分析上古汉语的“于”和“V于 NP” 结构，则和她存在着根本的分歧。本文指出，在“及物性假说”考虑的范围内，上古汉语“V 于 NP”结构中的“于”能引进受事。再来是句法问题。按动词的题元结构，上古汉语“V 于 NP”结构中的“于 NP”是动词的论元（Argument），它获得动词指派论旨角色（Thematic Roles）而跟动词产生语义联系。因此，在句法结构上，“V 于 NP”结构中的“于NP”投射在补足语（Complement）的位置，与谓语中心词共同组成最低层次的动词词组。The preposition “于”is multi-functional in old Chinese grammar. Previous studies merely listed its various functions, which makes it seem complicated. However, these studies have failed to provide a cohesive explanation for these functions of “于”. Based on Transitivity Hypothesis (Hopper & Thompson 1980), 董秀芳（2006）proposed that “于” in the “V于O” construction in old Chinese marks low transitivity between the verb and its nominal element. This contribution is to be credited. Yet, 董秀芳argued that “于” can introduce various nominal elements semantically in relation to the verb except for typical patient. Hence, “于” is syntactically a marker of “non-object” constituents and all the nominal elements introduced by “于” cannot be analyzed as objects. So much so that, the PP formed by “于” is located at V’ level functioning as adjunct, and all the nominal elements introduced by “于” are indirect themes (which represent subsidiary semantic roles such as location, reason, comparison etc.) to the predicate. We endorsed 董秀芳’s train of thought on the nature of “于”. However, our view on applying Transitivity Hypothesis and GB-theory to “于” and “V于O” in old Chinese differs from 董秀芳’s. We claim that “于” semantically introduces patient roles under the consideration of Transitivity Hypothesis. Based on argument structure and thematic roles, we claim that the PP formed by “于” (“于 NP”), is an argument to the predicate and it is assigned a thematic role. Hence, “于 NP” syntactically functions as a complement to the verb to form the VP at the bottom of the tree.